DAMPAK GEMPA BUMI LOMBOK TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI DESA KEKAIT KECAMATAN GUNUNG SARI KABUPATEN LOMBOK BARAT - Lalu Iwan Eko Jakandar (UIN Mataram, 2018)
This study aims to determine the impact or effect of the Lombok 2018 earthquake on the socio-economic life of the community in Kekait Village, Gunung Sari District, West Lombok Regency and find out the efforts made by the community in Kekait Village, Gunung Sari District, West Lombok Regency to rise from adversity due to the Lombok earthquake 2018 that happened. This study included research using a qualitative descriptive approach with a double embedded case study strategy. Data is taken from primary and secondary data. While the data sources in this study are informants or informants, events and activities as well as documents and archives. Test data validity is done by using data or source triangulation techniques and method triangulation. Data analysis uses interactive data analysis techniques with stages, namely: data collection, data reduction, data presentation, drawing conclusions and verification. The results of the study show that the impact of the earthquake on the Kekait Village community has had a tremendous impact on their lives. The August 5 2018 earthquake has a serious impact, especially the economic paralysis which results in every citizen living in an